In Hitler's shadow : West German historians and the attempt to escape from the Nazi past - Evans, Richard J. 1947- (Pantheon Books, 1989)
Richard J. Evans: In Hitler's Shadow. West German Historians and the Attempt to Escape from the Nazi Past. Pantheon Books, New York 1989. 196 Seiten, 16,95 Dollar